Mandatory Advance Notice of Layoff: Evidence and Efficiency Considerations - Jonas Cederlöf; Peter Fredriksson; Arash Nekoei; David Seim (Center for Economic Studies and ifo Institute (CESifo), 2021)
We investigate a prevalent, but understudied, employment protection policy: mandatory advance notice (MN), requiring employers to notify employees of forthcoming layoffs. MN increases future production, as notified workers search on the job, but reduces current production as they supply less effort. Our theoretical model captures this trade-off and predicts that MN improves production efficiency by increasing information sharing, whereas large production losses can be avoided by worker-firm agreements on side-payments – severance pay – in lieu of MN. We provide evidence of such severance increases in response to an extension of MN using novel Swedish administrative data. We then estimate the production gain of MN: extending the MN period leads to shorter non-employment duration and higher reemployment wages, plausibly driven by on-the-job search. Using variation in notice duration across firms, we estimate the productivity loss of notice. The estimates of benefits and costs suggest that MN has a positive net impact on production, offering an empirically-grounded efficiency argument for mandating notice.
Keywords: J31; J33; J63; J68; 330; unemployment; advance notice; job mobility; job quality